Impact of Capsaicin on Mast Cell Inflammation. (July 2013) - Frydas, S.; Varvara, G.; Murmura, G.; Saggini, A.; Caraffa, A.; Antinolfi, P.; Tetè, S.; Tripodi, D.; Conti, F.; Cianchetti, E.; Toniato, E.; Rosati, M.; et al.
Mast cells are inflammatory cells, and they are prominent in inflammatory diseases such as allergy and asthma. Mast cells possess high-affinity receptors for IgE (FCεRI) and the cross-linking of these receptors is essential to trigger the secretion of granules containing arachidonic acid metabolism [such as prostaglandin (PG) D2, leukotriene (LT) B4, and LTC4], histamine, cytokines, chemokines, and proteases, including mast cell-specific chymases and tryptases. Activation of mast cells provokes the secretion of cytokines and mediators that are responsible for the pathologic reaction of immediate hypersensitivity. Sensory nerve stimulation by irritants and other inflammatory mediators provokes the release of neuropeptides, causing an increase in vascular permeability, plasma extravasation and edema. Trigeminal nerve stimulation actives dura mast cells and increases vascular permeability, effects inhibited by capsaicin. Capsaicin causes release of sensory neuropeptide, catecholamines and vasodilation. Several studies have reported that capsaicin is effective in relief and prevention of migraine headaches, improves digestion, helps to prevent heart disease, and lowers blood cholesterol and blood pressure levels. The findings reported in these studies may have implications for the pathophysiology and possible therapy of neuroinflammatory disorders.